Effect of chicken litter biochar on phosphorus availability in acid soil and yield of zea mays L - Asap, Audrey (2017)
The reaction of H2PO42- and HPO4- with Al and Fe in acid soils to form a precipitate reduces diffusion of phosphorus into roots. The use of large amounts of lime and phosphorus fertilizers to saturate Al and Fe ions on acid soil so as to maintain sufficient supply of plant-available phosphorus is uneconomical. Biochar has been used to improve soil exchangeable phosphorus availability by decreasing soil acidity, Fe, and Al. However, there is limited information on the optimum rate of biochar and Triple Superphosphate (TSP) to increase phosphorus availability. The objectives of this study were to improve: (i) phosphorus availability in acid soils using TSP and chicken litter biochar and (ii) phosphorus uptake, agronomic efficiency, and yield of Zea mays L. Different rates of chicken litter biochar (25%, 50%, and 75%) of 5 t ha-1 and TSP (25%, 50%, and 75%) based on the recommended rate of 60 kg ha-1 phosphorus by MARDI were evaluated in incubation study (for 30, 60, and 90 days) and pot studies after which four promising treatments in the pot study were selected and evaluated in the field studies (first and second cycles). Selected soil physico-chemical properties, nutrient uptake, growth variable, and yield were determined using standard procedures. The incubation study results indicated that chicken litter biochar increased soil CEC and exchangeable K, Ca, Mg, and Na. Significant amounts of Al and Fe were fixed within the first 30 days of incubation suggesting that biochar can be used in tropical acid soils to reduced nutrients fixation by these ions. The results in the pot study showed that the maize plants in the soils amended with chicken litter biochar absorbed more of the phosphorus fertilizer and most of the absorbed phosphorus were translated into the crops dry matter production as compared with that of the normal fertilization. The use of 25% and 50% chicken litter biochar of 5 t ha-1 with 75% TSP increased maize plant dry matter more than that of the normal fertilization due increase in phosphorus availability thus, confirming the finding in the incubation study. Further evaluation of treatments with 25% and 50% chicken litter biochar of 5 t ha-1 with 75% TSP in the field increased maize grain yield (8.44 t ha-1) compared with normal fertilization (5.97 t ha-1). Phosphate fertilizer reduced in the first and second field trials by 63.9%. Chicken litter biochar use was also reduced by 75% and 50% of 5 t ha-1. These findings are also consistent with the findings in the incubation and pot study that, 25% and 50% biochar of 5 t ha-1 with 75% TSP is the optimum combination of chicken litter biochar and TSP to increase phosphorus availability, retention, phosphorus recovery and use efficiency, and maize grain yield.